Mesh ablator vs. cryoballoon pulmonary vein ablation of symptomatic paroxysmal atrial fibrillation: results of the MACPAF study - Koch, Lydia; Haeusler, Karl Georg; Herm, Juliane; Safak, Erdal; Fischer, Robert; Malzahn, U.; Werncke, Thomas; Heuschmann, Peter U.; Endres, Matthias; Fiebach, Jochen B.; Schultheiss, Heinz-Peter; Schirdewan, Alexander (Europace, 2012)
Aims Catheter ablation of the pulmonary veins (PVs) is a promising therapeutic approach for symptomatic atrial fibrillation (AF). The prospective randomized single-centre study ‘Mesh Ablator versus Cryoballoon Pulmonary Vein Ablation of Symptomatic Paroxysmal Atrial Fibrillation’ (MACPAF; clinicaltrials.gov NCT01061931) compared the efficacy and safety of two balloon-based PV ablation systems. Methods and results Thirty-two patients underwent PV ablation for symptomatic paroxysmal AF using the Arctic Front® or the HD Mesh Ablator® catheter according to study protocol. The primary endpoint was complete PV isolation (PVI) at the end of the ablation procedure, determined by exit block after achieving entrance block . Long-term follow-up data are not included in this publication. Patients’ mean age was 61.7 ± 8.9 years, 43.2% were female, and median CHA 2 DS 2 -VASc score was 2.0. In the intention-to-treat analysis, the rate of the primary endpoint was 56.5% in patients randomized to the Arctic Front® and 9.5% in patients randomized to the HD Mesh Ablator® catheter ( P = 0.001). In the per-protocol analysis, complete PVI was achieved in 13 (76.5%) of 17 Arctic Front® patients but in none of the 15 HD Mesh Ablator® patients ( P < 0.0001). There were one major and two minor complications in each study arm but no clinically evident stroke. Post-procedural AF recurrence was detected within hospital stay in two (11.8%) Arctic Front® patients and in seven (46.7%) HD Mesh Ablator® patients ( P = 0.049). Conclusion The MACPAF study revealed a superiority of the Arctic Front® catheter concerning complete PVI. Owing to the insufficient efficacy of the HD Mesh Ablator® catheter, the safety board decided to stop MACPAF prematurely.